Engineering the mechanical and biological properties of nanofibrous vascular grafts for in situ vascular tissue engineering. (17th August 2017) - Henry, Jeffrey J D; Yu, Jian; Wang, Aijun; Lee, Randall; Fang, Jun; Li, Song
Abstract: Synthetic small diameter vascular grafts have a high failure rate, and endothelialization is critical for preventing thrombosis and graft occlusion. A promising approach is in situ tissue engineering, whereby an acellular scaffold is implanted and provides stimulatory cues to guide the in situ remodeling into a functional blood vessel. An ideal scaffold should have sufficient binding sites for biomolecule immobilization and a mechanical property similar to native tissue. Here we developed a novel method to blend low molecular weight (LMW) elastic polymer during electrospinning process to increase conjugation sites and to improve the mechanical property of vascular grafts. LMW elastic polymer improved the elasticity of the scaffolds, and significantly increased the amount of heparin conjugated to the micro/nanofibrous scaffolds, which in turn increased the loading capacity of vascular endothelial growth factor (VEGF) and prolonged the release of VEGF. Vascular grafts were implanted into the carotid artery of rats to evaluate the in vivo performance. VEGF treatment significantly enhanced endothelium formation and the overall patency of vascular grafts. Heparin coating also increased cell infiltration into the electrospun grafts, thus increasing the production of collagen and elastin within the graft wall. This work demonstrates that LMW elastic polymer blending is an approach to engineer the mechanical and biological property of micro/nanofibrous vascular grafts for in situ vascular tissue engineering.